MENGEMBANGKAN DISPOSISI MATEMATIS SISWA SMP MELALUI PENDEKATAN PROBLEM POSING - Cut Man Farisyah (Universitas Jabal Ghafur, 2020)
Learning mathematics is not only aimed at developing mathematical cognitive abilities, but also for developing affective domains. One important aspect in the affective domain that is very influential and determines success in learning mathematics is the positive view of students on mathematics or in mathematics learning called mathematical disposition. A student who has a high disposition will be more persistent and resilient in facing mathematical problems that are more challenging and will be more responsible for their own learning and always develop good habits in mathematics. The problem posing approach which in the learning process requires students to ask questions and make their solutions is expected to be able to change students 'views of mathematics to be more positive, while also improving students' mathematical abilities. This study aims to examine the differences in the levels of mathematical disposition of junior high school students before and after learning through the problem posing approach. The type of research is experimental research with the design of one group pre-test post-test design. The population in this study were all VII grade students of Bandar Baru 1 Junior High School, with research samples of class VII2 students selected through random sampling techniques. The instrument used to obtain the research data was a mathematical disposition scale questionnaire sheet. The statistical test used to analyze data on differences in mathematical disposition of junior high school students before and after learning through the problem posing approach is paired t-test. The results showed that there were significant differences in the level of mathematical disposition of junior high school students before and after learning through the problem posing approach. This means that students' mathematical dispositions get better after they get a problem posing learning approach. Keywords: Mathematical Disposition, Problem Posing Approach